Adaptive Configuration Method of Low-Frequency Electromechanical Sampling Information in Building Electrical System - Bai Yu (Mathematical Problems in Engineering, 2021)
In order to enhance the reliability of the electrical systems in low frequency, an adaptive configuration method of low-frequency electromechanical sampling information based on thyristor controlled series compensation (TCSC) is designed. The electrical system is simplified to a linear invariant system, and a stochastic subspace identification (SSI) method is established by using the singular value decomposition principle to collect low-frequency electromechanical sampling information. The reference channel technology is introduced to design the reference channel covariance matrix to judge whether low-frequency information is generated and improve the efficiency of sampling information acquisition. The architecture and working principle of the controllable series compensation device are analyzed, and the test signal method is used to evaluate the low-frequency modes and the information required by the device among the electrical system regions of buildings. The alternative input signals are selected by comparing different input signal residue ratios. The TCSC device parameters are adjusted by the compensation residue phase method, so as to realize the adaptive configuration of different low-frequency electromechanical sampling information and ensure the stable operation of the electrical system. The experimental results show that the proposed configuration scheme can effectively improve the damping ratio of the system and has an excellent effect on suppressing the continuous oscillation under a low-frequency fault.